Évaluer une pratique innovante : essai réflexif autour de l’expression théâtrale - Marie-Noëlle Cocton (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
enThis article presents itself as a reflective essay on the evaluation of an innovative activity in French as a Foreign Language (FFL) class: the theatrical expression. Its objective is to question the concept of pedagogical innovation, considered as a new process, which has to be identified and analyzed in order to be made perceptible to the actors of teaching-learning. The first step is to understand the innovative dimension of this teaching-learning practice, both in its content and in its evaluation, before reporting, in a second step, on the metamorphoses described by the learners in their notebook. These transformations, which are linked with the content of the course, the activities, the learner in its relation to learning, the other and the self, play a role in nourishing and fostering reflection on the evaluation of pedagogical evaluation and on the actions to be taken in order to generate a new dynamic in the teaching and learning process.